Flat acoustics with soft gradient-index metasurfaces - Yabin Jin (Nature Portfolio, 2019)
Here, the authors report an approach for creating various acoustic wavefronts in free space by using soft gradient-index porous metasurfaces. These flat lenses generate steered planar, focused spherical and helical ultrasonic beams in water by manipulating the spatial distribution of the material porosity.